2021
DOI: 10.3390/microorganisms9061264
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Significance of SARS-CoV-2 RNA Dynamic in Naso-Pharyngeal Swabs

Abstract: From 16 March to 15 December 2020, 132,357 naso-pharyngeal/oropharyngeal swabs were collected in the province of Teramo, Abruzzo Region, Italy, and tested for the presence of SARS-CoV-2 genomic RNA by a commercially available molecular assay. A total of 12,880 swabs resulted positive. For 8212 positive patients (4.150 women and 4.062 men) the median age was statistically different between women (median: 49.55 ± 23.9 of SD) and men (median: 48.35 ± 23.5 of SD) while no differences were found in the comparison b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…5 That study demonstrated that by combining data from multiple cross sectional samples, population incidence can be estimated and longer-term incidence curves can be identified, without the use of more time and resource-intensive serologic surveillance studies. 5 The Pearson correlation coefficient in our study was similar to those of previous studies, 6 with an inverse relationship between Ct values and incident cases of SARS-CoV-2 hospitalization. Another study utilizing a larger number of Ct values showed a similar trend between Ct values and hospitalizations, with a Pearson correlation of −0.851 (P < .001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5 That study demonstrated that by combining data from multiple cross sectional samples, population incidence can be estimated and longer-term incidence curves can be identified, without the use of more time and resource-intensive serologic surveillance studies. 5 The Pearson correlation coefficient in our study was similar to those of previous studies, 6 with an inverse relationship between Ct values and incident cases of SARS-CoV-2 hospitalization. Another study utilizing a larger number of Ct values showed a similar trend between Ct values and hospitalizations, with a Pearson correlation of −0.851 (P < .001).…”
Section: Discussionsupporting
confidence: 89%
“…3,4 Recent studies have evaluated the use of Ct values as a more accurate method for estimating the epidemiologic trajectory of this pandemic. 5,6 Preliminary data suggest that when Ct values are higher, the epidemic appears to be in a waning phase, whereas when Ct values are trending lower, the epidemic may be growing. 5,6 We examined the association between Ct values from specimens collected over time at a tertiary-care emergency department with weekly state hospitalizations to evaluate the utility of using Ct to estimate epidemiologic trends and anticipate the next phase of the pandemic.…”
mentioning
confidence: 99%
“…However, the viral load decay speed was not significantly different between the cohorts, suggesting that the speed may be dependent on the basal viral load independently of the SARS-CoV-2 strain (Figure 2A,B). In line with this result, other studies evaluating the correlation between viral load and its decay over time found that higher amounts of virus detected in the nasooropharyngeal swabs were correlated to an increased viral persistence [27,28]. Moreover, the duration of the infection significantly differed between OSs carriers with different VLDS and these data were reinforced by the medium effect size obtained by comparing slow VLDS vs. medium/fast VLDS individuals (Supplementary Materials: Table S1).…”
Section: Discussionsupporting
confidence: 69%
“…During two epidemic waves the peak in viral load (determined by Ct) preceded the peak in positivity by 2–3 weeks Calistri et al. [ 21 ] 2021 Italy To analyze the trend of the Ct values in samples collected from March to mid-December 2020 Real-time Local Local There was a strong inverse correlation between Ct values and the trend in incident cases in the local population El Zein et al. [ 16 ] 2021 USA To evaluate the role of Ct values in samples as a prognostic marker in hospitalized patients Retrospective cohort study Single unit/local Regional A steady decrease in the percent of positive samples determined by Ct values was associated with the evolution of the pandemic from April to June 2020 Hay et al.…”
Section: Resultsmentioning
confidence: 99%